A Description of Antihypertensive Medication Adherence According to the Duration of Hypertension among Patients in the Working Area of Putri Ayu Primary Health Care, Jambi City - Fadhlan, M Fadhlan Wahyu Erlangga; Nurhusna; Sari, Putri Irwanti (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Introduction: Compliance with taking medication is the main determinant of treatment success. Hypertension is one of the most dangerous health problems in the world, because high blood pressure is a major risk factor that causes diseases such as stroke, heart failure, stroke and nephrosis. Objective: This study aims to determine the description of compliance with taking antihypertensive medication based on the length of time of suffering in hypertensive patients in the Putri Ayu Primary Health Care, Jambi City. Method: This study uses a descriptive quantitative method using a survey method. The population of this study was 31,615 people who visited the Putri Ayu Primary Health Care and consumed antihypertensive drugs in 2023, this sampling technique used a purposive sampling technique with 106 respondents. Results: The majority of respondents were aged between 46-65 years as many as 68 respondents (64.2%), the majority were female 58 respondents (54.7%), the majority had a high school education of 41 respondents (38.7%), the majority of respondents worked as housewives (IRT) 41 respondents (38.7%), Description of the level of compliance with taking antihypertensive medication in patients with new hypertension (<1 year) is mostly moderate at 10.4%. Description of the level of compliance with taking antihypertensive medication in patients with medium-term hypertension (1-5 years) is mostly low at 48.1%. Description of the level of compliance with taking antihypertensive medication in patients with long-term hypertension (> 5 years) is mostly low at 18.9%. Conclusion: The level of compliance of respondents based on the duration of treatment, the majority of respondents have a low level of compliance.